Evaluating strategies to improve glucosinolate concentration and root yield of field-grown horseradish in a Mediterranean environment: preliminary results - Rivelli, Anna Rita; Agneta, Rosa; Möllers, Christian; De Maria, Susanna (Italian Journal of Agronomy, 2016)
Horseradish is grown for its enlarged taproot that is widely used as a dish condiment and as a source of horseradish peroxidase. Nowadays, the species is gaining great interest due to the richness in bioactive compounds that besides providing a high nutritional value are tested for innovative applications in different fields. Nevertheless, the effect of crop management on root yield and glucosinolates (GLS) biosynthesis is poorly documented. Aim of this study was to evaluate the root yield and GLS concentration of two field-grown horseradish accessions (Cor and Mon) grown with nitrogen (N) alone and both N and sulphur (S) (-N-S, +N-S and +N+S treatments) and harvested at different times [late autumn (LA), 2011 and 2012, early spring (ES), 2012]. Yield increased throughout the harvests up to 48% on average of the fertilised treatments and 25% in the unfertilised control. Conversely, root GLS concentration significantly declined in the unfertilised control throughout the harvests [from 7.6 in LA_2011 to 1.43 Î¼mol/g dry matter (DM) in LA_2012] while it highly increased in plants grown with N alone and with both N and S by 46 and 98%, respectively, from LA_2011 to ES_2012 (up to 11.9 and 21.1 Î¼mol/g DM, respectively); then it drastically decreased by 80% on average, in the next harvest. Among individual GLS, the concentration of sinigrin and nasturtin similarly varied as effect of the analysed factors, showing the highest values in Cor accession. The data show that although the level of GLS is highly dependent on genotype, fertilisation and harvesting date may play a primary role in determining the yield and GLS concentration in horseradish root.